Tetrachloro-(acetylacetonato)stannate(IV) and tri-iodocadmate(II) stabilized by a heptacyclic cation: Synthesis, characterization, and crystal structure - Ndiolene, Adrienne; Diop, Tidiane; Boye, Mouhamadou Sembene; Diasse-Sarr, Aminata (European Journal of Chemistry, 2024)
The tin (IV) and cadmium (II) complexes were synthesized in mixture, the ligand 4,4’-(ethane-1,2-diylbis(azanylylidene))bis(pent-2-en-2-ol), and the halide metal (SnCl2 or CdI2). Complex synthesis involves partial hydrolysis of the ligand followed by condensation cyclization. The new tin complex obtained crystallizes in the monoclinic space group P21/n with a = 8.5468(5) Å, b = 17.9907(9) Å, c = 12.7227(7) Å, β = 94.220(5) °, V = 1950.98(18) Å3 and Z = 4. The asymmetric unit consists of an anion tetrachloro-(acetylacetonato)stannate(IV) and a heptacyclic cation. The geometry of the complex is octahedral with cis coordination of the two oxygens of the acetylacetone. The cadmium complex crystallizes in the orthorhombic space group Pbca with a = 14.7395(9) Å, b = 8.5914(5) Å, c = 23.2825(13) Å, V = 2948.3(3) Å3, Z = 8. The geometry around cadmium is a deformed tetrahedron. The heptacyclic cation and the anionic complex are interconnected through hydrogen bonding interactions, specifically N–H···Cl or N–H···I, forming a network.